Almost Lacunary Statistical and Strongly Almost Lacunary Convergence of order (?,?) of Sequences of Fuzzy Numbers - Braha, Naim latif; Et, Mikail; Altin, Yavuz (Univ Craiova, 2024)
The main purpose of this article is to introduce the concepts of almost lacunary statistical convergence and strongly almost lacunary convergence of order (beta,gamma) f sequences of fuzzy numbers with respect to an Orlicz function. We give some relations between strongly almost lacunary convergence and almost lacunary statistical convergence of order (beta,gamma) of sequences of fuzzy numbers, where beta and gamma are two fixed real numbers such that 0 < beta <= gamma <= 1.
Keywords: Fuzzy numbers; Almost statistical convergence; Orlicz function